Brief Report: Assessing Attitudes toward Culturally and Contextually Relevant Schoolwide Positive Behavior Support Strategies. (August 2015) - Fallon, Lindsay M.; O'keeffe, Breda V.; Gage, Nicholas A.; Sugai, George
Given the increased interest and implementation of Schoolwide Positive Behavior Support (SWPBS) systems in schools in the United States, practitioners and researchers have become interested in how to improve implementation with students and staff from a wide range of cultural backgrounds. Fallon, O'Keeffe, and Sugai (2012) reviewed the literature on behavior supports and culture and developed a list of recommended practices. To collect information on the perceived acceptability, feasibility, and efficacy of these practices, as well as accessibility to professional development on specific practices, we surveyed school staff members involved in SWPBS implementation across the country. Respondents (n = 330) indicated generally high agreement with the acceptability, feasibility, efficacy, and accessibility of training of culturally and contextually relevant SWPBS recommendations. Variations in these responses are discussed, and recommendations for research and practice are presented.